2001
DOI: 10.1016/s0168-6496(01)00142-8
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of impaired microcystin production for light-dependent growth and pigmentation of Microcystis aeruginosa PCC 7806

Abstract: Microcystis aeruginosa PCC 7806 produces potent inhibitors of eukaryotic protein phosphatases called microcystins, whose function to the organism is presently unknown. Mutants with impaired microcystin biosynthesis should provide a useful tool for investigations of microcystin function. This study has focussed on the comparison of growth and pigment content of strain PCC 7806 and its mcyB 3 mutant deficient in microcystin biosynthesis, under semicontinuous culture conditions. Both wild-type and mutant are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…The data also showed that mcyD transcripts initially increased when cells were transferred from 16 to 400 lmol photons m -2 s -1 (from low light to very high light) but decreased after 2 h (Kaebernick et al 2000). M. aeruginosa PCC7806 is a strain very sensitive to light, with saturating light intensities of about 32 lmol photons m -2 s -1 (Hesse et al 2006). Our study, using real time RT-PCR, shows that the increase not only occurs in light-saturating conditions, but mainly on transits to non saturating light conditions, 28 mol photons m -2 s -1 .…”
Section: Discussionmentioning
confidence: 80%
“…The data also showed that mcyD transcripts initially increased when cells were transferred from 16 to 400 lmol photons m -2 s -1 (from low light to very high light) but decreased after 2 h (Kaebernick et al 2000). M. aeruginosa PCC7806 is a strain very sensitive to light, with saturating light intensities of about 32 lmol photons m -2 s -1 (Hesse et al 2006). Our study, using real time RT-PCR, shows that the increase not only occurs in light-saturating conditions, but mainly on transits to non saturating light conditions, 28 mol photons m -2 s -1 .…”
Section: Discussionmentioning
confidence: 80%
“…Different types of oligopeptides may therefore well be able to replace each other indicating a linked function. This may also be an explanation for the observation that the knock-out of individual oligopeptides has no obvious consequence for the growth of cyanobacteria (Hesse et al, 2001;Repka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wiedner et al (2003) reported that intracellular microcystin content showed a significant linear positive correlation with growth rate under PAR (photosynthetically active radiation)-limited growth conditions but not under PAR-saturated growth conditions. It is worthy mentioning that the light saturation point for M. aeruginosa PCC 7806 is 32 µmol photon m −2 s −1 (Hesse et al 2001), which implies that, beyond this point, microcystin does not increase in concentration with the increase in light (Wiedner et al 2003). High light intensities may also stimulate passive release of microcystin from lysed cells, and its active export from living Microcystis cells (Schatz .…”
Section: Discussionmentioning
confidence: 99%